Spatial and Temporal Characterisation of Ecosystems in Landscapes Surrounding Granite Outcrops - Alibegovic, Goran (Curtin University, 2016)
This study develops and implements a methodology to map granite outcrops over the Southwest Western Australian Floristic Region using biannual Landsat TM imagery based on seasonal vegetation change. Ecosystem greenspots are mapped using a weighted seasonal summation of long term MODIS imagery to identify locations that may act as habitat refuges under climate change. Phenological characteristics on granite outcrop aprons are compared to non-apron areas to quantify habitat differences and responses to recent climate change.